TRANCEDENTAL COMMUNICATION (A SOCIO PHENOMENOLOGY PERSPECTIVE) - Yunitasari, Yunitasari (Universitas Prof. Dr. Moestopo (Beragama), 2009)
Phenomenological Sociology einphazing the subjective of· exctsttng g phenomena, which isfrom the seen socialfactthere is something urge individual so to take action for something that he believe. that is right. The phenomena doesnot refer lo the society in general, but refer to individual which sees human as agroup of individual which has different character as- well as has differentperception, attention. also interpretation. For example the movement of Al- Qiyadah Al-Islamiyah and Ahmadiyah Al-Qadiyan.